Electronic Versus Printed Book: A Comparison Study on the Effectivity of Senior High School Physics Book - Suyatna, A.; Maulina, H.; Rakhmawati, I.; Khasanah, R. A. N. (Jurnal Pendidikan IPA Indonesia, 2018)
This study aimed to examine the effectiveness of senior high school physics book both interactive electronic and printed, viewed from the difference in gender and material characteristics. The research used Quasi-Experimental Design with Non-Equivalent posttest-pretest control group design. The data were collected through physics tests from six senior high schools in Lampung Province, Indonesia and analyzed on ANOVA and multiple comparisons to determine the differences in learning outcomes (affectivity) and interaction between interactive electronic and printed, gender, and material characteristics. The results showed that there were different learning outcomes caused by interactive electronic and printed physics book (p=0.000<0.05). The learning outcomes using interactive electronic books were better than using printed books for both male and female students while gender differences did not affect physics learning outcomes for both interactive electronic and printed books (p=0.963>0.05). There was no interaction between interactive electronic and printed books and gender (p= 0.298>0.05). There are differences in learning outcomes caused by physical material characteristics (p= 0.000< 0.05). Therefore, it concluded that the high school interactive physics electronic book was effectively used as a learning resource for both male and female students.